Climate Change and the Convention Relating to the Status of Refugees of 28 July 1951 - Osóbka, Przemysław (Polish Review of International and European Law, 2021)
The article deals with The United Nations Convention relating to the Status of Refugees, Geneva, 28.7.1951 in the context of climate change consequences. Refuge is strictly defined category in the acts of international law. It does not include environmental and climatic reasons to leave one’s country of origin. However, in 1990, the Intergovernmental Panel on Climate Change (IPCC) drew attention to the fact that human migration could be one of the greatest effects of climate change. The author also analyzes the meaning of the provisions of Article 3 and Article 8 ECHR in the discussed area. The article tries to give an answer to the question whether and why it is necessary to apply the Geneva Convention to climate change refugees if they can be protected under core human rights treaties. It is of greatest interest to the extent where if refers to the climate change refugees situation in New Zeeland and Australia. These states seem to be pioneers in giving refugees protection due to climate change consequences. Probably adaptation of the 1951 Convention to the challenges facing the international community in connection with climate change will in itself become an expression of its responsibility for the consequences of these changes and their impact on individuals and entire communities.